Sinicizing Religions, Sinicizing Religious Studies - Benoît Vermander (Religions, 2019)
From 2015 onwards, “sinicizing religions„ has become the mantra of China’s religious policy, inspiring new regulations and constraining the functioning of religious organizations. After summarizing the “sinicization„ doctrine and policy, this paper examines how Chinese scholars in religious studies position themselves in such a context. It reviews the developments of the field after 1979; it appraises the complex interplay between the scholarly community and policy makers; it examines how scholars in religious studies now respond to the official policy, as they strive to balance descriptive and prescriptive assessments. It shows how the search for ideal-types as well as for ‘sinicized’ typologies and methodologies partly function as an adaptative tactic. The need to answer political imperatives revives older debates on religious forms and functions, and, to some extent, stirs theoretical imagination. However, political constraints make it difficult for scholars to focus on current religious trends, as they find it safer to debate on a somewhat atemporal model of “Chinese religion„.